The Validity and Readability of Ebook on Immune System to Upskill Students Scientific Literacy - Anindita Rahadinar Kinanti; Raharjo Raharjo (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Science literacy is very closely related to the era of the Industrial Revolution 4.0 which demands graduates of quality, able to compete globally and master the development of technology-based on information literacy. The quality of teaching materials such as books needs to be improved and developed in line with advances in information and communication technology. One effort that can be done to develop learning resources in the form of printed books is to package them in the form of electronic books. The purpose of this research was to develop an electronic book on Immune system materials to upskill students’ scientific literacy. This research was constructed as a development study using the 4D model (Define, Design, Develop, and Disseminate) but in this research we didn’t include a Disseminate step. Development stage was held in Biology Department of FMIPA Universitas Negeri Surabaya which produced Immune System e-book. Then, the developed electronic book was being assessed by two validators based on its construction requirements, technical requirements, and didactic requirements which include the scientific literacy aspects. Meanwhile the readability assessed by Fry Graphs. This Immune System e-book have 4 features, wish that it will help the students understanding and upskill the students scientific literacy. The results of the e-book’s validity based on its construction requirements, technical requirements, and didactic requirements were 3.9, 4, and 3.75 respectively. These results are categorized as valid and the e-book can be used in class without any significant revision. The readability assessments showed that the passages are suited for 9th‑grade, 10th grade, and 13th grade students. Even though the results are all in a difficult reading category which suits for high school students, revision needed to be done so that the passage in the e-book will specifically suits for 11th grade students. Keywords: Scientific Literacy, Validity and Readability